2021
DOI: 10.3390/jcm10184215
|View full text |Cite
|
Sign up to set email alerts
|

Burden of COVID-19 Pandemic Perceived by Polish Patients with Multiple Sclerosis

Abstract: People with multiple sclerosis (MS) were expected to be particularly affected by the COVID-19 pandemic. The purpose of the study was to evaluate the burden of pandemic, perceived by Polish MS patients, with regard to major contributing factors. The survey, conducted in August/September 2020, included: Perceived Stress Scale (PSS-10), Coping Orientations to Problems Experienced (Brief–COPE), questions on demographic data, MS characteristics, and health-related and social aspects of pandemic burden. Relationship… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…All studies were observational studies, being 45 (91.8%) cross-sectional studies and 4 (8.2%) longitudinal studies ( Table 1 ). Studies were done in Argentina ( 26 ), Australia ( 27–29 ), Chile ( 30 ), China ( 31 , 32 ), Cuba ( 32 ), Egypt ( 33 ), Kuwait ( 33 ), France ( 34 ), Iran ( 35–40 ), Italy ( 41–48 ), Montenegro ( 49 ), Poland ( 50 , 51 ), Portugal ( 52 ), Serbia ( 53 , 54 ), Spain ( 31 , 32 , 55 ), Turkey ( 56–58 ), and the United States of America ( 47 , 59–69 ). Most of the articles demonstrated to have reasonable methodological quality.…”
Section: Resultsmentioning
confidence: 99%
“…All studies were observational studies, being 45 (91.8%) cross-sectional studies and 4 (8.2%) longitudinal studies ( Table 1 ). Studies were done in Argentina ( 26 ), Australia ( 27–29 ), Chile ( 30 ), China ( 31 , 32 ), Cuba ( 32 ), Egypt ( 33 ), Kuwait ( 33 ), France ( 34 ), Iran ( 35–40 ), Italy ( 41–48 ), Montenegro ( 49 ), Poland ( 50 , 51 ), Portugal ( 52 ), Serbia ( 53 , 54 ), Spain ( 31 , 32 , 55 ), Turkey ( 56–58 ), and the United States of America ( 47 , 59–69 ). Most of the articles demonstrated to have reasonable methodological quality.…”
Section: Resultsmentioning
confidence: 99%
“…Among patients suffering from multiple sclerosis, a chronic and debilitating neurological disease, acceptance, planning and positive reframing strategies were shown to moderate the distress caused by the disease. It was suspected by the authors that a certain way of perceiving coping with the disease by patients with multiple sclerosis might be due to the fact that the main additional burden was the COVID-19 pandemic [40].…”
Section: Discussionmentioning
confidence: 99%
“…According to the General Health Questionnaire 28 (GHQ28) and PSS-10 scores, the highest intensity of symptoms was observed in patients with MS, while the kidney transplant recipients were the least likely to report complaints [ 19 ]. Further research in the MS group revealed over 80% of participants experienced high or moderate stress levels, which was more strongly correlated with social restrictions and interactions rather than the current condition resulting from the chronic disease [ 36 ]. In this comparison of coping strategies in four groups of chronically-ill patients, we link the previous results with potential higher sensitivity in patients with MS. We hypothesize that these patients are more likely to anticipate, observe and report even less substantial changes to their condition, which may be related to the progressive character of the disease.…”
Section: Discussionmentioning
confidence: 99%